Effect of Colloidal SIO2 Content on the Morphology of Coated Ceramic Particles - Shaiful Rizam Shamsudin; Mazlee Mohd Noor; Shamsul Baharin Jamaludin, Assoc. Prof. Dr.; Mohd Fitri Mohamad Wahid; Ruhiyuddin Mohd Zaki; Khairel Rafezi Ahmad; A.G.B. Syamsul; M. Harun; Y. Hafizal (Universiti Malaysia Perlis (UniMAP), 2008)
Organized by Universiti Malaysia Perlis (UniMAP), 9th - 12th June 2007 at Park Royal Hotel, Penang.